Size‐dependent Molecular Characteristics and Possible Sources of Organic Aerosols at a Coastal New Particle Formation Hotspot of East China. Issue 11 (2nd June 2021) - Wan, Yibei; Huang, Xiangpeng; Ge, Xinlei; Jiang, Bin; Liao, Yuhong; Yan, Qian; Shuai, Qin; Fu, Qinglong; Xiao, Hang; Yu, Huan
Abstract: We investigated size‐dependent molecular characteristics of coastal organic aerosols from <0.032 to 3.2 μm at a new particle formation (NPF) hotspot of east China by using Fourier transform‐ion cyclotron resonance mass spectrometry (FT‐ICR‐MS). Strong connection between C20–33 Hh Oo /C18, 30 Hh Oo Nn compounds in particles smaller than 0.10 μm and the volatile organic compounds emitted from local intertidal macroalgae suggests that the organic compounds (OC) in ultrafine particles are formed probably via the gas‐phase oxidation of long‐chain fatty aldehydes or acids, followed by particle‐phase accretion reactions or imine formation during the coastal NPF events. In 0.18–0.56 μm particles, dominant C8 –C20 CHO, CHON, CHOS and CHONS compounds (maximum: C10 or C15 ) are suggested most likely to be terpene oxidation products. Highly oxygenated compounds with 0.6 ≤ H/C ≤ 1.5 and 0.67 ≤ O/C ≤ 1.2 reside mostly in 0.18–0.56 μm particles, accounting for 5% of the OC formulas in this size range. Iodinated OC are subsequently formed via electrophilic substitution of non‐iodinated OC by iodine cations (e.g., from HOI or I2 ) in iodine‐rich particles. CHN and Cl/Br‐containing OC account altogether for only 0.7% and 0.9% of OC formulas, respectively. As a result of the above compound distribution, the intensity weighted unsaturation degree and carbon oxidation state of OC increase with particle size. The distribution of aromatic compounds (i.e. Aromaticity Index > 0.5) is bimodal with peaks in 0.056–0.18 μm and 1.0–3.2 μm. In addition, our study observed higher unsaturation degree, carbon oxidation state and aromaticity of OC in coastal PM2.5 than inland urban PM2.5 in the same region. Plain Language Summary: Organic aerosols contribute substantially to aerosol particles in the atmosphere. Their emission source and formation mechanism are expected to be very diverse in coastal atmosphere, with the contributions from both continental and marine sources. Ultra high resolution mass spectrometry technique helps us to tackle the complexity of this issue. With Fourier transform‐ion cyclotron resonance mass spectrometry, we determined the size‐dependent molecular composition, unsaturation degree, carbon oxidation state and aromaticity of organic aerosols at a coastal NPF hotspot of China. The analysis further attributed these coastal organic aerosols to intertidal macroalgae‐emitted volatile organic compound oxidation products, terpene oxidation products or electrophilic substitution reaction between organic compounds and iodine. Key Points: Fourier transform‐ion cyclotron resonance MS analysis revealed size‐dependent organic molecular compositions and possible sources at a coastal new particle formation hotspot Solid Phase Micro‐Extraction (SPME)‐GC‐MS analysis linked coastal ultrafine organic aerosols with volatile organic compound emission from local intertidal macroalgae We observed higher unsaturation degree, carbon oxidation state and aromaticity of organic aerosols in coastal PM2.5 than inland urban PM2.5